Criteria for Identifying Technically Difficult Cases when Performing Sacroiliac Intraarticular Injections Based on the Grade of Sacroiliac Arthrogram. Issue 10 (6th May 2020) - Kurosawa, Daisuke; Murakami, Eiichi; Aizawa, Toshimi; Watanabe, Takashi; Yabe, Yutaka
Abstract: Objective: An intraarticular sacroiliac joint (SIJ) injection cannot always be performed successfully. Based on the patterns of the sacroiliac arthrogram, we explored possible indicators of technically difficult and technically easy injections into the SIJ including demographic features and anatomical features evident on preprocedural imaging. Design: Observational study. Methods: We evaluated 76 patients with painful SIJ (total 108 joints) diagnosed by SIJ injections. The sacroiliac arthrogram was graded as follows: Grade (G) 0 = the margin of the joint was partially outlined; G1 = the margin was completely outlined; G2 = intraarticular space was substantially outlined; and G3 = intraarticular space was fully outlined. Two multivariable ordered logistic regression analyses were performed to test the relationships between gender, age, and Grade, as well as between computed tomography (CT) findings and grade. Results: In men, the totals by Grade were G0 = 8 (joints); G1 = 33; G2 = 3; and G3 = 0. In women, these were G0 = 4; G1 = 28; G2 = 22; and G3 = 10. The Grade was significantly higher in women and was also higher with age ( P  < 0.05). Regarding morphological features in CT, minor osteophytes increased the odds in favor of better Grades of arthrogram (odds ratio = 3.50). Substantial vacuum phenomena strongly increased the odds of better arthrograms (20.52). Conclusions: Outlining the SIJ cavity fully is significantly more difficult in male patients of any age than in aged female patients. The presence of minor osteophytes and substantial vacuum phenomena on preprocedure CT scans can be reasonably reassuring to the practitioner that they are unlikely to encounter difficulties during injection.